ПАТОГЕНЕТИЧЕСКОЕ И КЛИНИЧЕСКОЕ ОБОСНОВАНИЕ КОМПЛЕКСНОЙ ПРОФИЛАКТИКИ ГИПЕРГОМОЦИСТЕИНЕМИИ - М. Ю. Андрианова; Е. В. Ройтман; А. М. Исаева; И. М. Колесникова; М. В. Нуреев (SINAPS LLC, 2014)
Review is devoted to the role of vitamins B6 (pyridoxine), B9 (folic acid) and B12 (cyanocobalamin) in homocysteine metabolism as well as the effects of this vitamin complex for prophylaxis and treatment of hyperhomocysteinemia in cardiological, and neurological and obstetric practice. Unreasonableness of isolate folic acid usage without vitamins B6 and B12 to reduce homocysteine plasma levels and clinical consequences of such approach are noted. It is shown that parenteral administration of vitamin B complex (5 mg B6 + 1,05 mg B9 + 1,0 mg B12) is preferable in some clinical cases.